PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS KELAS V SD NEGERI 091374 NAGA SARIBU - Theresia Magdalena Br Tungkir; Patri Janson Silaban; Rumiris Lumban Gaol; Juliana; Dyan Wulan Sari HS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Think Pair Share type cooperative learning model on student learning outcomes in science learning on the food chain material of grade V of SD Negeri 091374 Naga Saribu Learning Year 2024/2025. The research method used is an experimental method with a quantitative research type. To obtain data, a test instrument of 20 questions and a 20 item questionnaire are required. The number of research samples is 21 students using a saturated sampling technique. To determine the initial ability of students, the study conducted a Pretest with an average value of 51,09 which is in the less category. The results of the Pretest have an increase from the results of the Posttest given previously with an average value reaching 77,1 with a good category. It can be said that the level of success of student learning outcomes using the Think Pair Share model has increased and has an effect with a strong category as evidenced by the results of the correlation coefficient test calculation obtained the results of rhitung ≥ rtable with a result of 0,756 ≥ 0.433. Furthermore, the hypothesis test that compares the value of thitung ≥ ttable. The value of thitung = 5,042 is obtained while ttable = 1,720. Because thitung ≥ ttable (5,042 ≥ 1,720) then Ha is accepted and Ho is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Think Pair Share learning model (X) on student learning outcomes (Y).